Complexity Study on the Unsteady Flow Field and Aerodynamic Noise of High-Speed Railways on Bridges - Jufeng Su; Yamin Sun; Yuyang Liu (Complexity)
To study complexity distributions of unsteady flow field and aerodynamic noise of a high-speed railway on bridges, an aerodynamic noise model of a railway was obtained. Meanwhile, detailed structures such as 6 bogies, 3 air conditioning units, 1 pantograph fairing, and 1 pantograph were considered. Numerical simulation was conducted to flow fields around the high-speed railway running on the bridge under a crosswind-free environment, with running speed of 350 km/h. Hence, unsteady flow behavior characteristics of the complete high-speed railway were obtained. Numerical simulation was conducted to noises of the railway on the bridge in combination with detached eddy simulation and acoustic analogy theory. Meanwhile, the broadband noise model was used for the quantitative analysis on distribution characteristics of the dipole noise source and quadrupole noise source of the high-speed railway on the bridge. Studied results proved that aerodynamic noise of the railway was caused by eddy shedding and fluid separation. Main noise sources of the high-speed railway include areas such as pantographs, train head streamline, bogies, windshield, and an air conditioning unit. Maximum sound pressure level and average sound pressure level of the high-speed railway on the bridge were 2.7 dBA and 2.3 dBA, respectively, more than those of the high-speed railway on a flat ground. On the bridge, the maximum sound pressure level of the pantograph on the bridge was 3.1 dBA larger than that on the flat ground. In addition, incoming flows of the high-speed railway on the bridge had greater impacts on aerodynamic noises around the railway compared with those of wake flows. Meanwhile, in directions of incoming flows and wake flows, linear relationship was between the sound pressure levels of noise monitoring points which had different distances from the train head nose and the logarithm of the distances.